FROM THEORY TO PRACTICE: AN ASSESSMENT OF PUTTING LEARNING INTO PRACTICE AMONG ALUMNI OF KOREA STUDIES, UNIVERSITY OF MALAYA - Hassan, Asmadi; Tan Soo Kee; Muhammad Muhsein Kamarudin; Rohayati Paidi (WILAYAH: The International Journal of East Asian Studies, 2023)
This article examines the application of learning among Korea Studies alumni, Department of East Asian Studies, Faculty of Arts and Social Sciences, University of Malaya. Among those are the application of Korean language at the work place, the application of Korean language in the higher degree programme and the application of Korean language in everyday life. In order to answer these questions, survey question method was adopted in this study to glean data for analysis and findings. Questionnaires were distributed to Korea Studies alumni from the first batch of graduates in 1999 until the recent one. The studies found that both knowledge of Korea Studies and language are important. Korean related course influences their way of thinking, open their mind and contributes to positive behaviour. The skills allow them to interact cross-culturally and understand the Korean mindset and their way of life. A good command of the language opens wider opportunities in career development as well. Currently, there are many employment opportunities for students proficient in Korean, from market research companies to social media outfits. Furthermore, post covid witnessed the rapid economic reconstruction of both Malaysia and South Korea and this resulted in the implementation of Regional Comprehensive Economic Partnership (RCEP) which opened more job opportunities in Malaysia. Therefore, graduates with Korean language skills can seize this opportunity and help the students to be competitive in the job market. The respondents suggested that students who wish to work with Korean companies be prepared with various language skills, such as taking a course in TOPIK Korean language before stepping into the real world.